Integrated Management of Faba Bean Viruses and Their Vectors in Lebanon - Kumari, Safaa; Choueiri, Elia; Moukahel, Abdulrahman; Kemal, Seid Ahmed (The International Association for the Plant Protection Sciences, 2024)
Faba bean viruses and their aphid vectors are major problems for Lebanese farmers, resulting in low faba bean productivity. Besides the direct harm, aphids (e.g. Aphis craccivora, A. fabae and Acyrthosiphon pisum) transmit devastating legume virus diseases. To save the crop and restore farmers’ confidence in growing faba bean, a field trial was conducted in the farmers’ fields to evaluate options for managing viruses and their aphid vectors during the 2023/2022 growing season. The options evaluated were: (i) three imported faba bean varieties (Italian, Moroccan and Spanish), (ii) two sowing dates (24 November 2022 and 5 January 2023), and (iii) faba bean seeds treatment with Celest top (25g/L difenoconazole + 25 g/L fludioxonil + 262.5 g/L thiamethoxam) at the rate of 1 cc/kg of seeds with untreated seeds as control. The experiment was conducted using split-factorial design in two replications. Results showed that the number of infected plants with viruses (yellowing, stunting, mosaic, mottling) and aphids were higher at the 2nd sowing date compared to the 1st sowing date, whereas viruses and aphids incidence were lower in the plots planted with treated seeds compared to the plots planted with untreated seeds and for both sowing dates. Moreover, no aphids were recorded in the plots planted with treated seeds for all three faba bean varieties sown in November (1st sowing date). Serological tests of the plants associated with virus symptoms revealed that 48 % of the plants were infected with Bean yellow mosaic virus (BYMV), 32 % with Chickpea chlorotic stunt virus (CpCSV) and 19 % with Faba bean necrotic yellows virus (FBNYV). FBNVY and CpCSV are transmitted by aphids in a persistent manner only, whereas BYMV is transmitted by aphids in a non-persistent manner as well as by seeds.